Coherent Beam Combination of Eight Watt-Level Polarization-Maintained Fiber Amplifiers - 周朴 王小林 马阎星 马浩统 许晓军 刘泽金 (Chinese physics letters, 2010)
We demonstrate the coherent beam combination of eight Watt-level polarization-maintained fiber amplifiers. The phase control signal of each amplifier is generated by running a stochastic parallel gradient descent algorithm on a digital signal processor （DSP）. The experimental result shows that the whole system in close-loop performs well for long-time observation. Energy encircled in the target pinhole is 6.68 times more than that in open-loop. The combination efficiency is as high as 84.5%.